The rising return to non-cognitive skill - Per-Anders Edin; Peter Fredriksson; Martin Nybom; Björn Öckert (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
We examine the changes in the rewards to cognitive and non-cognitive skill during the time period 1992-2013. Using unique administrative data for Sweden, we document a secular increase in the returns to non-cognitive skill. This increase is particularly pronounced in the private sector, at the upper-end of the wage distribution, and relative to the evolution of the return to cognitive skill. Sorting across occupations responded to changes in the returns to skills. Workers with an abundance of non-cognitive skill were increasingly sorted into abstract and nonroutine occupations, for example. Such occupations also saw greater increases in the relative return to non-cognitive skill. This suggests that the optimal skill mixes of jobs have changed over time, that there is sorting on comparative advantage, and that demand-side factors are primarily driving the evolution of the return to non-cognitive skill. Consistent with this, we also show that hikes in offshoring and IT-investments increase the relative reward to non-cognitive skill and the relative intensity of non-cognitive skill usage.
Keywords: J24; J31; 330; Wage inequality; sorting; skill returns; cognitive/non-cognitive skill